2022
DOI: 10.1002/aenm.202202984
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Nanotube‐Bridging Strategy for Integrating Single Fe Atoms and NiCo Nanoparticles in a Bifunctional Oxygen Electrocatalyst toward High‐Efficiency and Long‐Life Rechargeable Zinc–Air Batteries

Abstract: The development of highly efficient and robust bifunctional electrocatalysts for oxygen reduction (ORR) and evolution reactions (OER) is the key issue for realizing high‐performance and long‐life rechargeable zinc–air batteries (ZABs). However, it is still a great challenge to integrate independent ORR and OER sites in a catalyst with high activity. Here, a carbon nanotube‐bridging strategy is proposed to synthesize such a bifunctional oxygen electrocatalyst enriched with highly active single‐atom Fe sites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…(a) Overall polarization curves of CNSCo-500, CNSCo-600, and CNSCo-700 in 0.1 M KOH solution under the rotating rates of 1600 rpm; (b) comparison of Δ E (Δ E = E J10 – E 1/2 ) between CNSCo-600 and other catalysts, including FeMn-DSAC, FePc||CNTs||NiCo/CP, M-POPs, Fe 0.5 Co@HOMNCP, CoTAPP-PATA-COF, Ni-Co-Fe LDH, IE-NiFe/HPLIG, NiS/NiFe 2 O 4, Co 3 O 4 NSs/CC, CoCo 2 O 4 /NCNTs, Mo-O 2 S 2 -C, and Mn-RuO 2. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Overall polarization curves of CNSCo-500, CNSCo-600, and CNSCo-700 in 0.1 M KOH solution under the rotating rates of 1600 rpm; (b) comparison of Δ E (Δ E = E J10 – E 1/2 ) between CNSCo-600 and other catalysts, including FeMn-DSAC, FePc||CNTs||NiCo/CP, M-POPs, Fe 0.5 Co@HOMNCP, CoTAPP-PATA-COF, Ni-Co-Fe LDH, IE-NiFe/HPLIG, NiS/NiFe 2 O 4, Co 3 O 4 NSs/CC, CoCo 2 O 4 /NCNTs, Mo-O 2 S 2 -C, and Mn-RuO 2. …”
Section: Resultsmentioning
confidence: 99%
“…The depletion of fossil fuels, such as oil, coal, and natural gas, and global climate changes have motivated researchers worldwide to explore clean and sustainable energy sources. Rechargeable zinc-air batteries (ZABs) are one of the most promising energy technologies owing to their high theoretical capacity, environmental friendliness, low cost, and high safety. Unfortunately, their practical applications are still hindered by the limitations such as expensive cost, poor activity, and unstable air electrode catalysts toward both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the real active site for the OER was the corresponding hydroxide. 173 Wu et al constructed an NiFe LDH ( d -NiFe-LDH) with defects. Operando Raman spectroscopy confirmed that cation defects were gradually formed with an increase in the applied potential (VM → VMOH → VMOOH), indicating the structural change sequence of crystalline Ni(OH) x →disordered Ni(OH) x → NiOOH, which revealed the real electrocatalytic active sites.…”
Section: Study the Charging–discharging Mechanisms Of Air-cathodesmentioning
confidence: 99%
“…In this dual configuration, the low-electronegativity Zn atom donates an electron to Cu atoms and adjusts the d electron configuration of copper, ultimately benefiting the elongation and cleavage of O–O on the Cu active site and accelerating the ORR kinetics . Moreover, several recent studies have revealed that the coexistence of metal nanocluster/small nanoparticles and SACs can further boost the oxygen catalytic activity and stability of the active metal sites by regulating their geometric and electronic structures as well as enhancing the interactions between active sites and the supports, respectively. Huang et al reported that introducing nanoclusters (NCs) into SACs can effectively induce the electron redistribution and modulate the TM–N bond lengths, which promotes the desorption of intermediates during the ORR process . In addition, by designing a dual structure of FeN 4 sites and iron clusters, Wang et al showed that the iron clusters can optimize the adsorptive interaction of oxygen reduction intermediates on FeN 4 and simultaneously shorten the bond amplitude of FeN 4 , leading to an activity enhancement of FeN 4 sites by 60% .…”
Section: Introductionmentioning
confidence: 99%